(3GdHjGf aj GdLeY Hjf GdbUjOI hGdYfhGfs - (3jMji Hf CMeO Hf CMeO Hf UahGf Gdbjfj(B, (3GdCfOdSj GdeGdcj , J (B770 (3gs ((3CMeO Hf eMeO GdebQi Gdefhai GdTGaYi s)
(3ChdgG (B:s
(3bOe GdTjN GdEeGe GdMGaX GdebQj hdj Gddg JYGdi CHhGdbGSe GdTGWHj QMeg Gddg JYGdi aj bUjOJg s
(3BNQgG (B:s
(3hde jPcQ ef GdYfhGf eNGQL GdMQha hgj ePchQI aj GdbUjOI hHGddg GdJhajb cJGH GdHjGf aj GdLeY Hjf GdbUjOI hGdJjSjQ hGdYfhGf s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3QhGb GdCJQGc (B- (3GdCRgQ (B(354) s
Keywords: (3GdbQGAGJ hGdJLhjOs